THE EFFECT OF ENTREPRENEURSHIP EDUCATION AND INCOME EXPECTATIONS ON STUDENTS’ ENTREPRENEURIAL INTERESTS - Sitinjak, Ruth Theressa; Sumiati, Ati; Nurmalasari, Dewi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This study aims to analyze the influence of entrepreneurship education and income expectations on the entrepreneurial interest of students in the Administrative Economics Study Program at Jakarta State University. This study uses a quantitative method with an associative descriptive approach. Data were obtained through questionnaires and analyzed using Structural Equation Modeling (SEM) with the SmartPLS tool. The results show that partially, entrepreneurship education has a positive and significant effect on entrepreneurial interest. Income expectations also show a positive and significant effect on entrepreneurial interest. Both variables are able to explain 51.7% of the variability in entrepreneurial interest (adjusted R-square = 0.517). These findings indicate that entrepreneurship education and income expectations are important factors in shaping students' interest in becoming entrepreneurs. This study contributes to the development of more contextual entrepreneurship education strategies in public universities.